Desain Komunikasi Data Digital Pada Radio HF dengan Metode Frequency Shift Keying Berbasis Thonny Python - Haidir Fajar; Syamsul El Yamin; Masbah Siregar (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Digital data is one of the data or information that is often misused, therefore this research begins by studying various literatures related to the encryption system used in cryptographic techniques. And based on the literature that was read, made a series of design and encryption system design program based on Thonny Python. The results of the design are then realized by creating a series of file encryption systems through the application program. The results obtained from this study are the encryption system created in Thonny Python has been able to randomize the original information in this case in the form of a file and is able to transmit the encrypted data with various limitations. This study discusses digital data communication systems using HF radio waves with its main device as a complete communication radio with antenna and power supply, and is equipped with a Raspberry as an enhancement to digital data processing and FSK Modulator as an interface between Raspberry and HF radio that functions as a digital signal modifier that out of Raspberry becomes an analog signal as input for HF radio.